The Spirit of Compromise : Why Governing Demands It and Campaigning Undermines It - Updated Edition - Gutmann, Amy (Book collections on Project MUSE., 2014)
If politics is the art of the possible, then compromise is the artistry of democracy. Unless one partisan ideology holds sway over all branches of government, compromise is necessary to govern for the benefit of all citizens. A rejection of compromise biases politics in favor of the status quo, even when the rejection risks crisis. Why then is compromise so difficult in American politics today? In this book, the authors connect the rejection of compromise to the domination of campaigning over governing, the permanent campaign, in American democracy today. They show that campaigning for political office calls for a mindset that blocks compromise, standing tenaciously on principle to mobilize voters and mistrusting opponents in order to defeat them. Good government calls for an opposite cluster of attitudes and arguments, the compromising mindset, that inclines politicians to adjust their principles and to respect their opponents. It is a mindset that helps politicians appreciate and take advantage of opportunities for desirable compromise. The authors propose changes in our political institutions, processes, and mindsets that would encourage a better balance between campaigning and governing.